دراسة تحليلية لطرق تحديد التعرفة على نقل الركاب بالسيارات العامة والعوامل المؤثرة عليها - ديوب, محمد عباس (Latakia University Journal - Economic and Legal Sciences Series, 2019)
استعرضنا في هذا البحث مجموعة من القضايا الهامة التي تتعلق بالتعرفة على نقل الركاب بالسيارات العامة بالإضافة إلى تحليل تأثير مجموعة من العوامل على التعرفة . وقد ناقشنا مجموعة من الطرق المعروفة لتحديد التعرفة على وسائل نقل الركاب بالسيارات العامة وقمنا بتحليل عدة طرق أساسية، مع بيان إيجابياتها وسلبياتها ومدى تطبيقها في سوريا مع تقديم الاقتراحات المناسبة. وقد تم التركيز في دراسة طرق التعرفة على الطريقة التي تركز على العامل الأساسي وهو التكاليف (تكلفة النقل لراكب واحد ). وقد قمنا بتقديم مجموعة من المقترحات لتطوير هذه الطريقة آخذين بعين الاعتبار العوامل التي تعرضنا لها في الدراسة مع مراعاة المصالح الاجتماعية للسكان في النقل وأيضاً مصالح شركات (وسيلة) النقل. In this study, we deal with some important issues related to the fare of Transporting Passengers in public vehicles, in addition to analyzing the factors affecting the tariff. We discuss a group of known methods for assigning tariff in the public transportation and we analyze various basic methods, illustrating the advantages and disadvantages of these methods and the extent to which we can apply them in Syria, besides offering the appropriate suggestions. We concentrate on the method which takes into consideration the main factor, i.e. the cost of transporting one single passenger. We also offer a number of suggestions to improve this method, taking into consideration the factors mentioned in this research and the social welfare of the people in Transportation and the interests of the transport businesses.